Perancangan Interior Healthy Food Center dan Taman Hidroponik di Surabaya - Devina Felicia Luky (Intra, 2017)
A cafe is one type of business that is a lot of demand today. Designing the Interior Health Food Center and Hydroponics Park in Surabaya is a food and beverage service facility that offers a new atmosphere that will have a Hydroponic Park for children to adults and there is also a Supermarket that sells organic goods to meet the needs of the community. People today still do not know much about what is organic and consider organic food has a taste that is less delicious. Therefore the purpose of this interior design is in addition to as a place of entertainment and gathering, can also be means of education about how to start a healthy life with organic food, planting hydroponics plants and later can be direct though at the cafe.Scandinavian design style applied to rge design and the hydroponik garden with the concept offered in the overall atmosphere to be created is comfortable, relaxed, elegant and fresh